Dietary Patterns and Cognitive Decline in Chinese Elderly Singaporeans: A Longitudinal Cohort Study - Veronica Lee; Nazhir Adam (Sriwijaya Journal of Internal Medicine, 2024)
Introduction: Cognitive decline is a growing public health concern, especially among aging populations. Diet is a modifiable factor that can influence brain health. This study investigated the longitudinal association between dietary patterns and cognitive decline in Chinese elderly Singaporeans. Methods: A cohort of 1,500 community-dwelling Chinese adults aged ≥60 years in Singapore was followed for 6 years. Dietary intake was assessed at baseline using a validated food frequency questionnaire. Cognitive function was evaluated at baseline and biennially using a comprehensive neuropsychological battery assessing memory, attention, executive function, and language. Dietary patterns were identified using factor analysis. Linear mixed-effects models were used to examine the association between dietary patterns and cognitive trajectories, adjusting for confounders. Results: Three dietary patterns emerged: "Traditional Chinese" (high in rice, vegetables, and fish), "Western" (high in red meat, processed foods, and sugary drinks), and "Prudent" (high in fruits, vegetables, whole grains, and low-fat dairy). Adherence to the "Prudent" pattern was associated with a slower decline in global cognition, memory, and executive function. The "Western" pattern was associated with a faster decline in memory and executive function. The "Traditional Chinese" pattern was not significantly associated with cognitive decline. Conclusion: A "Prudent" dietary pattern may protect against cognitive decline in elderly Chinese Singaporeans. Promoting healthy dietary habits may be an effective strategy for preserving cognitive function and promoting healthy aging.